Timor-Leste Water Sector Assessment and Roadmap - World Bank Group (World Bank, Washington, DC, 2018)
Despite significant progress since gaining independence in 2002, Timor-Leste’s economy is still struggling with declining oil revenues and slowing economic growth, while access to improved basic services is still low and vulnerability to natural disasters remain high. In that context, strategic investments in the water sector and addressing water management is crucial to meet national and international development commitments and to stimulate economic growth. Potential for the development of the water resources exists in Timor-Leste, although it is constrained by limited data as well as by the institutional capacity to implement integrated water resources management (IWRM) solutions. Irrigation scheme rehabilitation has been driven by a target of self-sufficiency in food production but recent studies point to alternatives and more economically viable models for achieving this policy target. For water supply and sanitation, Timor-Leste met its millennium development goal (MDG) water and sanitation targets for urban areas, but missed its MDG target for rural areas. Progress has been made, although the sustainability of services remains a challenge. Investing in the water sector will have broad and significant benefits to the economy, community, and the environment in Timor-Leste.